GAME ONLINE’S EFFECTS TO EMOTIONAL AND SOCIAL DEVELOPMENT ON ULA’S PUPILS - Wahyudi, Iman; Sabat, Yulianto (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The study aims to find out how online gaming affects the emotional and social development of ULA Sekolah Setara (basic). The method in this research uses a qualitative approach. The study targeted pupils of the ULA (basic) school age who played online games with a total of five children. The data collection techniques used in this study were three-day observations and interviews. Based on the results of interviews and observations done on five (5) ULA (basic) pupils who use online gaming, researchers found both positive and negative influences. These positive influences include learning about technology, understanding the various applications of online games, and learning new vocabulary in foreign languages. As for the negative influence of online games on the emotional and social development of children, children are more irritable, more aggressive, and lack interaction with the people around them.